Pengaruh Tunneling Incentive, Bonus Mechanism, dan Debt Covenant Terhadap Transfer Pricing - Shalsabila Herman; Dirvi Surya Abbas; Hamdani Hamdani (Akuntansi, 2023)
The purpose of this study is to determine the effect of tunneling incentive, bonus mechanism and debt covenant on transfer pricing in consumer goods industry companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the period 2016-2020. The sampling technique uses purposive sampling technique. Based on the established criteria, 10 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that Bonus Mechanism and Debt Covenant have no effect on Transfer Pricing, Tunneling Incentive has no influence on Transfer Pricing.